A Vector-Based Algorithm to Differentiate Septal and Free Wall Sites of Origin of Ventricular Arrhythmias in the Right Ventricular Outflow Tract - Zhang, Fengxiang; Xu, Yan; Fang, Zhen; Zhao, Liyan; Yang, Bing; Chen, Hongwu; Ju, Weizhu; Toorabally, Mohammad; Cao, Kejiang; Chen, Minglong (International Journal of Heart Rhythm, 2016)
Purposes: There are few vector-based electrocardiogram (ECG) algorithms to differentiate ventricular tachycardia (VT) and premature ventricular complexes (PVCs) originating from the septum (SP) or free wall (FW) in the right ventricular outflow tract (RVOT). Methods: One hundred and twenty-one patients (mean age 41 ± 13 years; 62% female) underwent mapping and ablation of symptomatic PVC or VT with left bundle branch block morphology. Inferior axis and precordial lead transition zone ≥V3 on the ECG were analyzed retrospectively. Ablation was highly successful on the 95 SP patients and among 26 cases in the FW group. The ECG morphology of VT/PVC was analyzed to derive a novel algorithm to localize VT origin within the RVOT. A VT/PVC QRS axis ≥90° or an R wave amplitude ratios ≥1 in leads II and III predicted a septal origin. If neither of these characteristics were present, the following criteria were each given a score of 1: VT/PVC QRS axis <85;°, leads II and III R wave amplitude ratio <0;.88, QRS duration in lead III ≥155 ms, and QRS duration ≥155 ms in lead aVL. A cumulative score of ≥2 predicted an FW origin whereas a total score of <2; predicted an SP origin. A prospective analysis in 99 patients was used to confirm the significance of the algorithm. Results: Retrospective analysis showed that the new algorithm predicted an SP origin with an overall sensitivity, specificity, and positive predictive values of 95.2%, 88%, and 96.3%, respectively. Prospective analysis showed that the new algorithm predicted RVOT-SP origin with a sensitivity, specificity, and positive predictive values of 97.5%, 88.9%, and 97.5%, respectively. Conclusion: The new vector-based ECG algorithm can differentiate septal from FW sites of origin in the RVOT with a high sensitivity, specificity, and positive predictive values.